2012
DOI: 10.1515/jpm-2011-0231
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous iron treatment in pregnancy: comparison of high-dose ferric carboxymaltose vs. iron sucrose

Abstract: Objective: Oral iron substitution has shown to be insuffi cient for treatment of severe iron defi ciency anemia in pregnancy. Ferric carboxymaltose is a new intravenous (i.v.) iron formulation promising to be more effective and as safe as iron sucrose. We aimed to assess side effects and tolerance of ferric carboxymaltose compared to i.v. iron sucrose in pregnant women. Methods:We performed a retrospective analysis of 206 pregnant women who were treated either with ferric carboxymaltose or iron sucrose for iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
5
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(136 citation statements)
references
References 22 publications
6
119
5
6
Order By: Relevance
“…Both were effective and no SAEs were observed. Similar results in 206 gravidas were obtained in a comparison between FCM and IS [61].…”
Section: Administration Of Parenteral Iron In Practicesupporting
confidence: 75%
“…Both were effective and no SAEs were observed. Similar results in 206 gravidas were obtained in a comparison between FCM and IS [61].…”
Section: Administration Of Parenteral Iron In Practicesupporting
confidence: 75%
“…13 Among other comparative studies, none demonstrated any statistically significant differences between groups across any perinatal outcomes investigated, including birth weight, gestational age, method of delivery, and postpartum haemorrhage. 11,14,16,24,30,31,37,38,54,56 Notably, the small study samples included in each of these studies limited the statistical power to detect clinically relevant differences between the two groups.…”
Section: Perinatal Outcomesmentioning
confidence: 85%
“…women; 41 studies ), FCM (n = 276 women; four studies 13,[52][53][54] ) and IPM (n = 164 women; three studies [55][56][57] ).…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations